2004
DOI: 10.1021/jp048933v
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO2on Model Surfaces of Cesium Oxides Determined from First Principles

Abstract: Gradient-corrected periodic density functional theory was used to examine the bulk and low index surfaces of several cesium oxides (Cs 2 O, Cs 2 O 2 , and CsO 2 ). The adsorption of CO 2 on those surfaces was explored. The cesium-terminated {001} surface of Cs 2 O had a weak affinity for CO 2 with an adsorption strength of only -4.1 kJ mol -1 . In contrast, the Cs 2 O {010} surface exposing both Cs and O atoms adsorbed CO 2 with a strength of -284 kJ mol -1 . The adsorption of CO 2 in the bridged configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Thus, the X–O distances were close to the sum of the X + and O 2− atomic radii, namely 2.41 Å for Na + +O 2− , 2.77 Å for K + + O 2− , 2.91 Å for Rb + + O 2− , and 3.06 for Cs + + O 2− , as also observed for the X–O distances in crystalline metal oxides, for example, 2.40 Å in Na 2 O [ 43 ], 2.79 in K 2 O [ 43 ], 2.92 in Rb 2 O [ 43 ], and 3.26 Å in CsO 2 [ 44 ]. These findings indicate that the electrostatic interaction between O and X was strong and similar to the ionic bonding between O and X in X 2 O. Wang et al found that for oxygenate species adsorbed on K + -modified Cu (111) and Cu (110) surfaces, when the distance between K and O atoms was 3.00 Å, direct bonding between O δ− and K δ+ ions occurred [ 22 ].…”
Section: Resultssupporting
confidence: 63%
“…Thus, the X–O distances were close to the sum of the X + and O 2− atomic radii, namely 2.41 Å for Na + +O 2− , 2.77 Å for K + + O 2− , 2.91 Å for Rb + + O 2− , and 3.06 for Cs + + O 2− , as also observed for the X–O distances in crystalline metal oxides, for example, 2.40 Å in Na 2 O [ 43 ], 2.79 in K 2 O [ 43 ], 2.92 in Rb 2 O [ 43 ], and 3.26 Å in CsO 2 [ 44 ]. These findings indicate that the electrostatic interaction between O and X was strong and similar to the ionic bonding between O and X in X 2 O. Wang et al found that for oxygenate species adsorbed on K + -modified Cu (111) and Cu (110) surfaces, when the distance between K and O atoms was 3.00 Å, direct bonding between O δ− and K δ+ ions occurred [ 22 ].…”
Section: Resultssupporting
confidence: 63%
“…[16] Among a variety of materials reported in this category, this section describes in detail adsorption on a representative oxide, calcium oxide, along with a discussion of other important metal-based adsorbents including magnesium oxides and lithium zirconates. Although we focus attention here on calcium oxides and magnesium oxides, it should be noted that many other metal oxides display some CO 2 adsorption properties under selected conditions including lithium oxides, [98] sodium oxides, [99][100][101][102] potassium oxides, [103,104] rubidium oxides, [105] cesium oxides, [106] barium oxides, [107] iron oxides, [108][109][110][111][112] tantalum oxides, [113] copper oxides, [114,115] chromium oxides, [116][117][118][119][120] and aluminum oxides. [121][122][123][124][125][126] where M can be, for example, Mg, Ca, Sr, Ba.…”
Section: Metal-based Adsorbentsmentioning
confidence: 99%
“…There have been numerous studies focusing on the interaction of CO 2 with oxide surfaces. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Baltrusaitis et al 9 observed the formation of carbonate and bicarbonate species upon CO 2 adsorption on g-Al 2 O 3 surfaces. Rosynek identified that, for CO 2 adsorption on g-Al 2 O 3 , carbonate was the dominant surface species at high temperatures (>150 C) and low CO 2 coverages, whereas bicarbonate was formed at low temperatures (<150 C) and high CO 2 coverages.…”
mentioning
confidence: 99%